Trauma and seronegative spondyloarthropathy: rapid joint destruction in peripheral arthritis triggered by physical injury. Issue 1 (January 1988) - Olivieri, I; Gherardi, S; Bini, C; Trippi, D; Ciompi, M L; Pasero, G
Abstract : Two B27 positive patients developed peripheral arthritis immediately after a significant musculoskeletal injury. Unlike previously reported peripheral arthritis precipitated by trauma in B27 positive subjects the arthritis was rapidly destructive.